Effectiveness of initiating extrafine-particle versus fine-particle inhaled corticosteroids as asthma therapy in the Netherlands. Issue 1 (December 2016) - van der Molen, Thys; Postma, Dirkje; Martin, Richard; Herings, Ron; Overbeek, Jetty; Thomas, Victoria; Miglio, Cristiana; Dekhuijzen, Richard; Roche, Nicolas; Guilbert, Theresa; Israel, Elliot; van Aalderen, Wim; et al.
Abstract Background Most randomised clinical trials typically exclude a significant proportion of asthma patients, including those at higher risk of adverse events, with comorbidities, obesity, poor inhaler technique and adherence, or smokers. However, these patients might differentially benefit from extrafine-particle inhaled corticosteroids (ICS). This matched cohort, database study, compared the effectiveness of extrafine-particle with fine-particle ICS in a real-life population initiating ICS therapy in the Netherlands. Methods Data were from the PHARMO Database Network, comprising pharmacy and hospital discharge records, representative of 20 % of the Dutch population. The study population included patients aged 12 − 60, with a General Practice-recorded diagnosis for asthma (International Classification of Primary Care code R96), when available, ≥2 prescriptions for asthma therapy at any time in their recorded history, and receiving first prescription of ICS therapy as either extrafine-particle (ciclesonide or hydrofluoroalkane beclomethasone dipropionate [BDP]) or fine-particle ICS (fluticasone propionate or non-extrafine-particle-BDP). Patients were matched (1:1) on relevant demographic and clinical characteristics over 1-year baseline. Primary outcomes were severe exacerbation rates, risk domain asthma control and overall asthma control during the year following first ICS prescription. Secondary outcomes, treatment stability and being prescribed higher versus lower category of short-acting β2 agonists (SABA) dose, were compared over a 1-year outcome period using conditional logistic regression models. Results Following matching, 1399 patients were selected in each treatment cohort (median age: 43 years; males: 34 %). Median (interquartile range) initial ICS doses (fluticasone-equivalents in μg) were 160 (160 − 320) for extrafine-particle versus 500 (250 − 500) for fine-particle ICS (p  < 0.001). Following adjustment for residual confounders, matched patients prescribed extrafine-particle ICS had significantly lower rates of exacerbations (adjusted rate ratio [95 % CI], 0.59 [0.47–0.73]), and significantly higher odds of achieving asthma control and treatment stability in the year following initiation than those prescribed fine-particle ICS, and this occurred at lower prescribed doses. Patients prescribed extrafine-particle ICS had lower odds of being prescribed higher doses of SABA (0.50 [0.44–0.57]). Conclusion In this historical, matched study, extrafine-particle ICS was associated with better odds of asthma control than fine-particle ICS in patients prescribed their first ICS therapy in the Netherlands. Of importance, this was reached at significantly lower prescribed dose.